Nazi occultism : between the SS and esotericism - François, Stéphane 1973- (Routledge studies in fascism and the far right, 2023)
"Nazi Occultism" provides a serious scholarly study of a topic that is often marred by sensationalism and misinformation. - "The Morning of the Magicians" by Pauwels and Bergier (1960) gave rise to the idea that a secret society with wide powers, the "Thule society", was the hidden and ignored centre of Nazism. The influence of this very real small group is, however, only a fantasy, a myth. The author, a historian specializing in neo-Nazism, looks back on this speculative construction, its origins, its ideological tinkering, and the practices which have succeeded in forming a sort of radical and sulphurous counterculture which has created a fascination with esotericism and Nazism and the SS. To better understand it, he also paints a portrait of some of the authors who contributed to this extremist subculture, such as the Italian esotericist Julius Evola, the Argentine anthropologist Jacques-Marie de Mahieu, Chilean neo-Nazi Miguel Serrano, and the writer Jean-Paul Bourre. - This book will appeal to scholars, researchers, and activists as well as general readers with an interest in the history of Nazism and the occult